Respuesta :

29i (A.) hope this helps 

Answer:

The value of the (2 – 5i)(p + q)i is 29i .

Option (a) is correct .

Step-by-step explanation:

As the expression given in the question.

= (2 - 5i) (p + q)i

Simplify the above

= (2 - 5i) (pi + qi)

= 2pi + 2qi - 5pi²- 5qi²

As i² = -1

Put in the above

= 2pi + 2qi + 5p +5q

= 2i × 2 + 2i × 5i + 5 × 2 + 5 × 5i

= 4i + 10i² + 10 + 25i

As i² = -1

= 4i - 10 + 10 + 25i

= 29i

Thus the value of the (2 – 5i)(p + q)i is 29i .

Option (a) is correct .